(untitled) (Mongolian Journal of Agricultural Sciences, 2014)
In recent years, many researchers have stated the importance of above and belowground interactions to better understand succession in plant communities and state and transition dynamics in rangelands. A review indicate that improved knowledge the soil’s seed bank is a key element in understanding above and belowground interactions and plant community dynamics in grazed rangelands. The aim was to study current successional theories, with special emphasis on state and transition models to understand rangeland ecosystem dynamics under grazing. I thoroughly reviewed 28 articles published that summarized and provided specific values on similarities between above and belowground communities to identify under grazing across different ecosystem DOI: http://dx.doi.org/10.5564/mjas.v11i2.243 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.191-196